Scoping study of the Honduran coffee supply chain: Challenges and opportunities - Ceballos-Sierra, Federico; Wiegel, Jennifer; Gómez, Miguel; Colindres, Mirian (International Food Policy Research Institute, 2024)
This scoping study delves into the critical aspects of the coffee industry in Honduras, a major global coffee producer. It explores the significant growth in Honduran coffee production and productivity, while contrasting these achievements with rising environmental and social sustainability concerns. Key issues include the impact of climate change on coffee suitability, increasing rural poverty despite growing export values, and the challenges in maintaining consistent coffee quality and fair profit distribution along the supply chain. The study aims to review the agricultural policy context, describe the global coffee value chain (GVC), and identify constraints hindering production efficiency and inclusivity. It proposes interventions focusing on vertical coordination, quality improvement, digital innovations for traceability, and market information access, with special emphasis on environmental sustainability and gender and youth inclusion. The study utilizes an extensive literature review and inter views with sector stakeholders to analyze the dynamics within the Honduran coffee supply chain, identifying critical bottlenecks and potential solutions. The findings highlight issues in informal labor markets, oligopsonistic market conditions, and the need for improved contracting between international buyers and domestic sellers. The study sets the stage for detailed examination and intervention strategies in subsequent sections, aiming to enhance the overall performance and sustainability of the Honduran coffee industry.